ANALYSIS OF PARKING RETRIBUTION MANAGEMENT IN SOLOK CITY - Rosalina, Lusi (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2014)
Retribution is one of useful source revenue to finance the development of theregion.Solok city as a small-town poor probed Natural Resources, try to delve of its existing potentials. One of them is Parking Retribution Management. Management of Parking Levy in Solok city was originally carried out by a third party through a cooperation agreement with the aim of lowering costs incurred, even until the released of the regulationNo. 5, 2008 parking management is still carried out by a third party. However, the implementation of the retribution often doesn?t reach the determined targets. In 2011 the management of public parking on the roadsidewas managed by the Department of Transportation to increase parking fees revenuerapidly. Based on the above explanation, the purpose of this research is to analyze the procedures, mechanisms and analyze the performance of the management of parking charges before and after the implementation of Regulation No. 5 of 2008. This research method is descriptive of quantitative, whereas, descriptive analysis is used to describe the growth of the economy parking retribution. Meanwhile,quantitative analysis calculate the level of efficiency and effectiveness performance on management of public parking on the road, as well as a comparative analysis that compares the parking levy revenue growth before and after the implementation of the regulations. The research result on management of roadside parking fees, there are different procedures, and mechanismsmanagementwhich is managed by third parties and by Department of Transportation, while the performance of management retribution in public parking on the roadside is more effective and efficient than when managed by a third party